The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/2321-1407.148014
|View full text |Cite
|
Sign up to set email alerts
|

Current status of temporomandibular joint disorders and the therapeutic system derived from a series of biomechanical, histological, and biochemical studies

Abstract: This article was designed to report the current status of temporomandibular joint disorders (TMDs) and the therapeutic system on the basis of a series of clinical, biomechanical, histological and biochemical studies in our research groups. In particular, we have focused on the association of degenerative changes of articular cartilage in the mandibular condyle and the resultant progressive condylar resorption with mechanical stimuli acting on the condyle during the stomatognathic function. In a clinical aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…In healthy TMJ joints, the disc acts as a stress absorber, while enabling cooperative movement with condylar repositioning during jaw movement. When exceeding stress affects the joint, disc displacement may occur with transmission to the surrounding tissues [ 46 ]. As the TMJ is—apart from the knee and clavicular joints—the only synovial joint with an articular disc, research in this topic reveals important insights in understanding osteoarthritis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy TMJ joints, the disc acts as a stress absorber, while enabling cooperative movement with condylar repositioning during jaw movement. When exceeding stress affects the joint, disc displacement may occur with transmission to the surrounding tissues [ 46 ]. As the TMJ is—apart from the knee and clavicular joints—the only synovial joint with an articular disc, research in this topic reveals important insights in understanding osteoarthritis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…When exceeding stress affects the joint, disc displacement may occur with transmission to the surrounding tissues [ 46 ]. As the TMJ is—apart from the knee and clavicular joints—the only synovial joint with an articular disc, research in this topic reveals important insights in understanding osteoarthritis [ 46 ]. TMJ OA is an important disease in orthodontics and a fundamental factor in the reduction of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] The condylar position was more posterior in anterior disk displacement with reduction, and more concentric and anterior in anterior disk displacement without reduction. 33 Yang et al selected a total of 52 TMJs with the anterior, concentric and posterior condylar position. 14 They traced the condylar movements by simulating mandibular movements with 3D CT data and a position tracking camera.…”
Section: Discussionmentioning
confidence: 99%
“…Our results regarding the relationship between mandibular first molar position and the condyle-glenoid fossa suggested that the condylar height was smaller when the mandibular first molar showed greater distal movement, and the glenoid fossa simultaneously moved deeper. Tanne et al 26 showed that the great compressive stresses produced in the anterior and lateral regions of the mandibular condyle subsequently increased with the vertical skeletal discrepancy. The decrease in condylar height and increase in glenoid fossa depth might be due to the stresses between the condyle and glenoid fossa exerted during the process of mandibular molar distal movement.…”
Section: Discussionmentioning
confidence: 99%